An autobiographical history of Ethno Sweden: a testimonial about its origins, underlying ideology and initial goals (Orfeu, 2019)
Ethno is a multicultural summer camp for young musicians interested in traditional, folk and world music which began in Sweden in 1990 and continues today, having spread over 15 countries in the last decade. It is characterized by its peer-to-peer learning approach whereby young people teach each other the music from their countries and cultures. This article reconstructs part of the history of Ethno Sweden through an autobiographical report written by its founder, Magnus Bäckström, about the origin, ideology, strategies, and organization of the event. Interviews with the current organizer, Peter Ahlbom, complement this report detailing the organization of the event after Magnus’ departure, the process of its affiliation to the non-governmental organization Jeunesses Musicales International, and its expansion to other countries. Information is given about how the organization of Ethno Sweden went from the Falun Folkmusic Festival to Rikskonserter (Concerts Sweden) and then to Folkmusikens Hus in Rätvik.
Keywords: Ethno Sweden; Summer camp; Folk Music; Traditional Music; World Music